2010
DOI: 10.1152/japplphysiol.01202.2009
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral contributions to neuromuscular fatigue induced by a 24-h treadmill run

Abstract: This experiment investigated the fatigue induced by a 24-h running exercise (24TR) and particularly aimed at testing the hypothesis that the central component would be the main mechanism responsible for neuromuscular fatigue. Neuromuscular function evaluation was performed before, every 4 h during, and at the end of the 24TR on 12 experienced ultramarathon runners. It consisted of a determination of the maximal voluntary contractions (MVC) of the knee extensors (KE) and plantar flexors (PF), the maximal volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
167
5
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(199 citation statements)
references
References 39 publications
(53 reference statements)
14
167
5
5
Order By: Relevance
“…Considering previously published literature, we could speculate a role of fatigue in determining a reverse J-shaped pacing strategy 1,2,26 . In 24-h race simulations on a treadmill, speed declined regularly from the beginning until 16 h (similar to our study) and remained constant afterwards (different) 23,24 . Martin et al 23 showed a large maximal muscle torque reduction after the 24-h trial and an increase in ratings of perceived exertion (RPE)-from the beginning until 16 h, tending to plateau around 15 points afterwards.…”
Section: General Pacing Strategy and Performance Group Differencessupporting
confidence: 87%
See 1 more Smart Citation
“…Considering previously published literature, we could speculate a role of fatigue in determining a reverse J-shaped pacing strategy 1,2,26 . In 24-h race simulations on a treadmill, speed declined regularly from the beginning until 16 h (similar to our study) and remained constant afterwards (different) 23,24 . Martin et al 23 showed a large maximal muscle torque reduction after the 24-h trial and an increase in ratings of perceived exertion (RPE)-from the beginning until 16 h, tending to plateau around 15 points afterwards.…”
Section: General Pacing Strategy and Performance Group Differencessupporting
confidence: 87%
“…In 24-h race simulations on a treadmill, speed declined regularly from the beginning until 16 h (similar to our study) and remained constant afterwards (different) 23,24 . Martin et al 23 showed a large maximal muscle torque reduction after the 24-h trial and an increase in ratings of perceived exertion (RPE)-from the beginning until 16 h, tending to plateau around 15 points afterwards. Concomitantly, Gimenez et al 24 showed an increase in oxygen uptake until 8 h, again, followed by a plateau.…”
Section: General Pacing Strategy and Performance Group Differencessupporting
confidence: 87%
“…Large central fatigue (i.e. reduced maximal voluntary activation) was observed after running 5-24 h (Millet et al 2002a(Millet et al , b, 2011bPlace et al 2004;Martin et al 2010), while the development of peripheral fatigue is generally confined to a moderate level. In addition to a slight but significant reduction in neural drive, muscular factors are widely involved in the velocity deterioration during single (400 m, Tomazin et al 2011) or repeated (12 9 40 m, Perrey et al 2010) running sprints.…”
Section: Introductionmentioning
confidence: 99%
“…2 Poststroke fatigue is known to persist for months to years. 8,9 The time elapsed since the stroke occurred does not explain levels of fatigue. 2,10 Two years after a stroke approximately 40% of patients report that they are "always" or "often" fatigued.…”
mentioning
confidence: 99%
“…7,8 Fatigue, by its very definition, involves behavioral and work performance decrement and is characterized by distress and decreased functional status related to reduced energy. 11 Poststroke fatigue often poses a barrier to return to work and reduced physical function, daily activities, quality of life, and rehabilitation potential.…”
mentioning
confidence: 99%